THE IMPORTANCE OF DISCOURSE MARKERS - Xamidova Mashxura Abror qizi; Teshaboyeva Nafisa Zubaydulla qizi (Ustozlar uchun, 2025)
Effective communication goes beyond the mere use of correct grammar or an extensive vocabulary. It involves how well ideas are organized, connected, and conveyed. Discourse markers are one of the key elements that ensure smooth, coherent, and natural speech. Despite being small and sometimes overlooked, discourse markers play a crucial role in making spoken language more fluent and comprehensible.